2007
DOI: 10.1097/qad.0b013e3282ef1bb4
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease in HIV infection: an urban epidemic

Abstract: Kidney disease is an important complication of HIV, particularly in minority populations. We describe the burden of chronic kidney disease among 1239 adults followed at an urban AIDS center, with an estimated prevalence of 15.5% (n = 192). Independent predictors of kidney disease included older age, black race, hepatitis C virus exposure, and lower CD4 cell count. These data suggest that chronic kidney disease remains a common complication of HIV infection in the era of antiretroviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
119
6
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(139 citation statements)
references
References 11 publications
8
119
6
6
Order By: Relevance
“…HIV-infected persons are at higher risk for proteinuria, CKD, and ESRD compared with uninfected individuals, even after controlling for traditional kidney disease risk factors (1)(2)(3)(4)(5)(6). However, standard clinical measures of kidney disease, such as serum creatinine and dipstick proteinuria, are inadequate in their ability to detect early kidney damage (7).…”
Section: Introductionmentioning
confidence: 99%
“…HIV-infected persons are at higher risk for proteinuria, CKD, and ESRD compared with uninfected individuals, even after controlling for traditional kidney disease risk factors (1)(2)(3)(4)(5)(6). However, standard clinical measures of kidney disease, such as serum creatinine and dipstick proteinuria, are inadequate in their ability to detect early kidney damage (7).…”
Section: Introductionmentioning
confidence: 99%
“…Krawczyk et al had found in the United States that taking anti-hypertensive treatment is a factor associated with chronic kidney failure (p=0.004) [18]. It's important to note also that hypertension is one of the criteria used by the Infectious Diseases Society of America (IDSA) to describe HIV patients with a high risk of developing kidney disease [19].…”
Section: Prevalence Of Chronic Kidney Failure In People With Hivmentioning
confidence: 99%
“…The risk of both acute kidney injury and chronic renal disease is increased in human immunodeficiency virus (HIV) patients compared with the general population [1]. After the introduction of highly active antiretroviral treatment (HAART), arterial hypertension, diabetes, atherosclerosis and drug toxicity are gaining relevance in the HIV patient as risk factors for the development of kidney disease.…”
Section: Introductionmentioning
confidence: 99%